2013
DOI: 10.1345/aph.1r530
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis of Thromboembolic Events in Patients with Nephrotic Syndrome

Abstract: When patients with NS are admitted to the hospital, develop an acute medical illness, or acquire an additional thrombotic events risk factor such as surgery, active malignancy, or pregnancy, consideration for primary pharmacologic prophylaxis with appropriately dosed low-molecular-weight heparin or other indicated anticoagulant should include the potential for increased thrombotic events risk in this patient population. Consideration may also be given to the use of primary pharmacologic prophylaxis with low-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 46 publications
0
35
0
Order By: Relevance
“…Prophylactic treatment could include anticoagulants (for a recent review about anticoagulants in adult patients with NS, see Pincus et al [84]), but also antiplatelet agents such as acetylsalicylic acid [85]. Some early reports theoretically support the use of antiplatelet medication, showing normalization of in vitro platelet aggregation in NS during treatment with acetylsalicylic acid [23,39].…”
Section: Potential Of Antiplatelet Therapy In Nephrotic Syndromementioning
confidence: 99%
“…Prophylactic treatment could include anticoagulants (for a recent review about anticoagulants in adult patients with NS, see Pincus et al [84]), but also antiplatelet agents such as acetylsalicylic acid [85]. Some early reports theoretically support the use of antiplatelet medication, showing normalization of in vitro platelet aggregation in NS during treatment with acetylsalicylic acid [23,39].…”
Section: Potential Of Antiplatelet Therapy In Nephrotic Syndromementioning
confidence: 99%
“…19 Moreover, heparin also could dissolve thrombus. 20,21 Proteinuria is one of the main characterizations of kidney diseases, the results of this study showed that low-molecularweight heparin calcium showed good curative effect on proteinuria. Fukui et al 22 conducted one controlled clinical trial in pediatric patients with moderate systems of HSP, their research also showed that intravenous administration of factor XIII concentrate, 30-50 U/kg for days, was associated with significant improvements in the severity of proteinuria and hematuria compared with a non-treated group.…”
Section: Discussionmentioning
confidence: 70%
“…The mechanism by which nephrotic syndrome causes a hypercoagulable state is unclear but is posited to be secondary to loss of proteins, including anticoagulants such as antithrombin III, plasminogen, protein C, and protein S. 11 The incidence of thromboembolism in nephrotic syndrome is not well defined but is estimated to be between 2% and 42% for venous thrombosis and between 2% and 8% for arterial thromboembolism. 12 The incidence of thromboembolism appears to be highest in the first 6 months following the diagnosis of nephrotic syndrome. 10 Patients with severe hypoalbuminemia (< 2 g/dL) and those with membranous nephropathy have the greatest risk of thromboembolic complications.…”
Section: Discussionmentioning
confidence: 99%
“…10 Patients with severe hypoalbuminemia (< 2 g/dL) and those with membranous nephropathy have the greatest risk of thromboembolic complications. 12 Although controversial, some experts recommend primary prophylaxis with anticoagulants in patients with nephrotic syndrome, particularly for those with severe hypoalbuminemia. 12 Patients with IgA nephropathy appear to have the lowest risk of thromboembolic complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation